DEVELOPING FUNCTIONAL LITERACY OF STUDENTS BASED ON THE PISA INTERNATIONAL RESEARCH (Ustozlar uchun, 2025)
This article explores the development of functional literacy among students based on the findings of the Programme for International Student Assessment (PISA) research. PISA focuses on assessing students’ ability to apply their knowledge and skills in real-life situations. The study examines the importance of functional literacy as a key competence for success in the modern world and analyzes how PISA results highlight various aspects of student performance in reading, mathematics, and science. The paper discusses the implications of PISA findings for curriculum development and teaching strategies, emphasizing the need for a shift from traditional rote learning to more practical, problem-solving approaches. Additionally, it looks at the role of educators, policymakers, and educational systems in fostering functional literacy and preparing students for future challenges.